The relationship between positive illusion and performance skill level among female athletes of Aphrodite Sports club - Abdullah, Musab Mohammed; Abdullah, Sazgar Haji (Universitas Tanjungpura, 2025)
Background and Study Aim. Athletic performance is influenced by various psychological factors, including positive perception illusions that increase confidence, which in turn impact motivation and consistency of performance. Understanding how these illusions relate to performance will provide insight into effective psychological interventions for female athletes. This study examines the relationship between positive illusions and skill performance levels among female athletes at the Aphrodite Sports Club. The study also developed and validated two measurement tools: the Positive Illusion Scale (34 items, 5 dimensions) and the Skill Performance Test (SPT), which evaluates technical, tactical, and physical performance in basketball, volleyball, and futsal.Material and Methods. A descriptive correlational approach was used with 89 female athletes (basketball: n = 24, volleyball: n = 35, futsal: n = 30). The SPT consists of three phases: Preparation (4 points), Main Execution (4 points), and Optional Elements (2 points). Validity and reliability analyses confirmed strong content validity (CVR = 0.86), test-retest reliability (r = 0.89, 0.87, 0.88), and inter-rater reliability (ICC = 0.91, 0.89, 0.90). Assisted analysis using SPSS 26 Application.Results. Statistical analysis (ANOVA, t-test, Pearson correlation) shows that positive illusions are significantly correlated with skill performance (r = 0.62, p <0.001). Basketball players outperform futsal players (p = 0.025), while volleyball players show intermediate performance. Unrealistic optimism had the highest score (3.85), while positive future expectations had the lowest score (3.52).Conclusion. These findings highlight that self-enhancing beliefs can improve confidence, decision-making, and performance stability, and this study recommends integrating psychological training and standardized skill assessments into sports programs. Future research is recommended to explore the long-term effects of positive illusions on performance.